Effect of Carboxy Methyl Cellulose Addition with Glycerol Plasticizer on Physical Properties of Taro-based Biodegradable Plastics - Urwatil Wuskha; Ratnawulan Ratnawulan; Gusnedi Gusnedi (Journal of Experimental and Applied Physics, 2023)
Widespread use of synthetic plastics that are not biodegradable and made from non-renewable petrochemical sources endangers the environment. Using biopolymers like starch, gluten, and guar gum to create biodegradable plastics is one way to reduce the use of synthetic plastics. One of the materials that can be used as biodegradable is taro starch. This study's goal was to ascertain how adding carboxymethyl cellulose (CMC) concentration affected the physical characteristics of taro-based biodegradable plastic. This sort of study is experimental, with the concentration of carboxymethyl cellulose (CMC) added as the independent variable and the mass of starch, glycerol plasticizer, distilled water, and sample thickness of 0.24 mm as the controls. Tests carried out include tensile strength and elongation tests as well as water resistance tests and tests of the ability of biodegradable plastics to degrade in soil. This study involved altering CMC by up to 15%, 20%, 25%, 30%, and 35% (w/w starch) while using up to 5 grams of taro starch as the mixing material and up to 3 ml of glycerol plasticizer as the plasticizer concentration. The test findings demonstrated that adding starch with a CMC concentration of up to 35% w/w had an impact on the plastic's tensile strength and elongation values. The percentage of weight loss of biodegradable polymers increases when CMC concentration is added, and the level of water resistance decreases when CMC concentration is added in amounts up to 35% w/w starch.